2022
DOI: 10.1017/s0033291722000332
|View full text |Cite
|
Sign up to set email alerts
|

Mental health across the early years in the military

Abstract: Background The mental health impact of the initial years of military service is an under-researched area. This study is the first to explore mental health trajectories and associated predictors in military members across the first 3–4 years of their career to provide evidence to inform early interventions. Methods This prospective cohort study surveyed Australian Defence personnel (n = 5329) at four time-points across their early military career. Core outcomes were psychological distress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…In contrast, a secondary analysis of the Millennium Cohort, a prospective population-based study of U.S. military personnel prior to operations in Iraq and Afghanistan in 2001, showed that nearly 8 out of 10 military personnel maintained a stable score (around 20 points) on the PCL-C scale, which translates as a consistent level of resilience seven years after their military deployment [ 37 ]. Another descriptive study in Australian servicemen also reported that the majority exhibited resilient characteristics, and the mean score on the PCL-4 remained at a minimum (around 4 points out of 20) four years after the start of military service [ 38 ]. In addition, those who started with higher PTSD symptom severity and then experienced a considerable decrease in PCL-4 score (from 8 to 6 points out of 20) showed a higher frequency of self-blaming (OR = 2.09; 95% CI = 1.91–2.29), risk-taking (OR = 1.97; 95% CI = 1.70–2.29), and avoidance (OR = 1.79; 95% CI = 1.55–2.06) coping styles [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, a secondary analysis of the Millennium Cohort, a prospective population-based study of U.S. military personnel prior to operations in Iraq and Afghanistan in 2001, showed that nearly 8 out of 10 military personnel maintained a stable score (around 20 points) on the PCL-C scale, which translates as a consistent level of resilience seven years after their military deployment [ 37 ]. Another descriptive study in Australian servicemen also reported that the majority exhibited resilient characteristics, and the mean score on the PCL-4 remained at a minimum (around 4 points out of 20) four years after the start of military service [ 38 ]. In addition, those who started with higher PTSD symptom severity and then experienced a considerable decrease in PCL-4 score (from 8 to 6 points out of 20) showed a higher frequency of self-blaming (OR = 2.09; 95% CI = 1.91–2.29), risk-taking (OR = 1.97; 95% CI = 1.70–2.29), and avoidance (OR = 1.79; 95% CI = 1.55–2.06) coping styles [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…A secondary analysis of the Millennium Cohort, a prospective population-based study of U.S. military personnel prior to operations in Iraq and Afghanistan in 2001, showed that nearly 8 out of 10 military personnel maintained a consistent level of resilience seven years after their military deployment [ 37 ]. Another descriptive study of Australian servicemen also reported that the majority exhibited resilient characteristics four years after the start of military service [ 38 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results largely supported a linear relationship between social network size and mental health outcomes; the only exception was soon after soldiers returned from deployment (discussed below). Our findings dovetail with recent observations that resilient mental health trajectories in the first several years of military servicei.e., those characterized by stable, low psychological distress or posttraumatic stress symptomsare predicted by increased social support from family, friends, and military peers and leaders (Dell et al, 2022). Identifying new recruits or soldiers preparing for deployment who report particularly impoverished social networks could allow for early intervention targeting mechanisms hypothesized to underpin social disconnection.…”
Section: Discussionmentioning
confidence: 99%
“…A number of scientific papers on predicting the adaptation of military personnel to service show that most of them adapt well, but some people have some difficulties of varying degrees, which can manifest themselves in the form of increased stress and mental disorder [2,6,11,21]. Studies of scientists from the Netherlands have demonstrated that the rate of adaptability in servicemen was higher than that in civilians [20].…”
mentioning
confidence: 99%